APPLICATION OF ANTITHYMOCYTE GLOBULIN IN CHILDREN AFTER CADAVER KIDNEY TRANSPLANTATION. RETROSPECTIVE ANALYSIS - V.A. Goryainov; M.M. Kaabak; N.N. Babenko; A.K. Zokoev; E.A. Molchanova; L.A. Shishlo; M.M. Morozova (Union of pediatricians of Russia, 2011)
The article provides results of in-house research to assess the impact of induction immunosuppression using antithymocyte globulin (ATG) on the clinical course of post-transplantation period after kidney transplantation. The authors analysed 260 allotransplantations of cadaver kidneys (215 children). In some children (n = 25) the medicine was used for induction therapy, in some (n = 10) to suppress steroid-resistant rejection. Patients in the control group (n = 189) were not administered ATG. The highest actuarial survival rate (both transplants and patients) was recorded in the group of children where ATG was used for induction therapy, rather than just for treatment of rejection.Key words: induction therapy, allotransplantation of kidney, antithymocyte globulin, survival rate, children.